Primary cytoreductive surgery for advanced stage endometrial cancer: a systematic review and meta-analysis - Albright, Benjamin B.; Monuszko, Karen A.; Kaplan, Samantha J.; Davidson, Brittany A.; Moss, Haley A.; Huang, Allan B.; Melamed, Alexander; Wright, Jason D.; Havrilesky, Laura J.; Previs, Rebecca A. (American journal of obstetrics and gynecology, 2021)
Endometrial cancer uncommonly presents at an advanced stage and little prospective evidence exists to guide the management thereof. We aimed to summarize the evidence about primary cytoreductive surgery in the treatment of advanced stage endometrial cancer. MEDLINE, Embase, and Scopus databases were searched from inception to September 11, 2020, using search terms representing the themes “endometrial cancer,” “advanced stage,” and “primary cytoreductive surgery.” We included full-text, English reports that included ≥10 patients undergoing primary cytoreductive surgery for advanced stage endometrial cancer and that reported on the outcomes of primary cytoreductive surgery and survival rates based on the residual disease burden. Two reviewers independently screened the studies and with disagreements between the reviewers resolved by a third reviewer. Data were extracted using a standardized form. The percentage of cases reaching maximal (no gross residual disease) and optimal (<1 cm or <2 cm residual disease) cytoreduction were assessed by summing binomials proportions, and the association with survival was assessed using an inverse variance-weighted meta-analysis of logarithmic hazard ratios. From 1219 unique records identified, 34 studies were selected for inclusion. Studies consisted of single or multi-institutional cohorts of patients collected over a period of 6 to 24 years and included various mixes of histologies (endometrioid, serous, clear cell, and carcinosarcoma) and disease stages (III or IV). In a meta-analysis of the extent of residual disease after primary cytoreductive surgery, we found that 52.1% of cases reached no gross residual disease status (n=18 studies; 1329 patients) and 75% reached <1 cm residual disease status (n=27 studies; 2343 patients). The proportion of cytoreduction for both thresholds was lower for studies of stage IV vs stage III to IV disease (41.4% vs 69.8% for no gross residual disease; 63.2% vs 82.2% for <1 cm residual disease) but did not vary notably by histology. In a meta-analysis of the reported hazard ratios, submaximal (any gross residual disease vs no gross residual disease) and suboptimal (≥1 cm vs <1 cm) cytoreduction thresholds were associated with worse progression-free survival (submaximal hazard ratio, 2.16; 95% confidence interval, 1.45–3.21; I2=68%; suboptimal hazard ratio, 2.55; 95% confidence interval, 1.93–3.37; I2=63%) and overall survival rates (submaximal hazard ratio, 2.57; 95% confidence interval, 2.13–3.10; I2=1%; suboptimal hazard ratio, 2.62; 95% confidence interval, 2.20–3.11; I2=15%). Sensitivity analyses limited to high-quality studies demonstrated consistent results. Among cases of advanced stage endometrial cancer undergoing primary cytoreductive surgery, a significant proportion of patients are left with residual disease, which is associated with worse survival outcomes. Further investigations about the roles of neoadjuvant chemotherapy and primary cytoreductive surgery in prospective trials is warranted in this population.